2012
DOI: 10.1186/1687-1499-2012-366
|View full text |Cite
|
Sign up to set email alerts
|

4-ary network coding for two nodes in cooperative wireless networks: exact outage probability and coverage expansion

Abstract: The fact that sensor nodes are powered by limited-capacity batteries makes power efficiency; one of the most critical issues in wireless sensor networks (WSNs). Advanced communication techniques combined with network coding and cooperative schemes have attracted considerable attention as ways to improve power efficiency in wireless transmission as well as to achieve high throughput and spectral efficiency in WSNs. In this study, we consider cooperative wireless networks with two nodes and one base station, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…(16) Next, the exact outage probability with NBNC-4 for N1 is obtained by adding the results so far, i.e., (8), (12), (14), and (16), as follows:…”
Section: B Outage Probabability For Nbnc-4 and Bncmentioning
confidence: 99%
See 2 more Smart Citations
“…(16) Next, the exact outage probability with NBNC-4 for N1 is obtained by adding the results so far, i.e., (8), (12), (14), and (16), as follows:…”
Section: B Outage Probabability For Nbnc-4 and Bncmentioning
confidence: 99%
“…Using nonbinary network coding (NBNC) with GF(q) for q > 2, it was shown that a full diversity order can be achieved [10] and [11]. In addition, for aspects of power efficiency techniques, a couple of benefits of the use of NBNC has been found in [12] as expansion of deployment of source nodes without increasing transmit power.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, as in the case of conventional cooperation, the application of network coding techniques in the cognitive radio context is expected to be beneficial. Indeed, the authors in evaluate the outage probability for a two users network with the use of a GF(4) non‐binary network code. The results show that the proposed scheme achieves full diversity order, and the coverage area can be expanded by the use of network coding without increasing the transmit power.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have since been devoted to clarifying if the network coding provides advantages over existing cooperative network schemes [3]- [11]. Chen et al [3] have shown that, assuming perfect inter-user channels, binary network coding based on the arithmetic of the Galois field of size 2, i.e., GF (2), can provide improved diversity gain and bandwidth efficiency in wireless networks when each user employs a simple decode-and-forward scheme.…”
Section: Introductionmentioning
confidence: 99%